Inhibited growth of mesenchymal stem cells under simulated microgravity - Quynh Chi, Ho Nguyen; Quang Huy, Hoang Nguyen; Chinh Chung, Doan; Nghia Son, Hoang; Thanh Long, Le (Vietnam Journal of Biotechnology, 2020)
This study aimed to estimate the effects of simulated microgravity (SMG) on mesenchymal stem cells (MSCs). The 3D clinostat was applied to induce to simulated microgravity on MSC. The results showed that the MSC density in control group was higher than the SMG group. The cell cycle analysis demonstrated that the MSC ratio in G0/G1 phase in SMG group was higher than that of the control group, while the MSC ratio in S phase and G2/M phase in SMG group was lower than those of the control group. The real time quantitative RT-PCR was used to evaluate the expression of cell cycle-related genes, including Cyclin-dependent kinase 2 (Cdk2), Cyclin-dependent kinase 6 (Cdk6), and Cyclin A. The results showed that the transcript expression of Cdk2, Cdk6, and Cyclin A was down-regulated in MSC from SMG group comparing to that of the control group. The flow cytometry was performed to determine the ratio of apoptotic MSCs. There was no significant difference in viability ratio and apoptotic ratio of MSCs between SMG group and control group. The MSCs from SMG group and control group showed similar in Bcl2 and Bax transcript expression.